2022
DOI: 10.3390/biomedicines10030548
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect and Induced Immune Response Following Exposure of Hexaminolevulinate and Blue Light in Combination with Checkpoint Inhibitor in an Orthotopic Model of Rat Bladder Cancer

Abstract: Previous studies have found that use of hexaminolevulinate (HAL) and blue light cystoscopy (BLC) during treatment of bladder cancer had a positive impact on overall survival after later cystectomy, indicating a potential treatment effect beyond improved diagnostic accuracy. The aim of our study was to determine whether HAL and BL mimicking clinically relevant doses in an orthotopic rat model could have therapeutic effect by inducing modulation of a tumor-specific immune response. We also assessed whether admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…They observed an anti-tumor effect and an indication of immune activation following HAL-BLC according to visual assessment of immunological markers (CD3 + , CD8 + , and CD4 + ), with observation of intratumoral CD3 + and CD8 + immune cell infiltration. However, quantification of the total number of CD3 + cells revealed significantly higher CD3 + infiltration in the control group than in the HAL-BLC group, but similar results were not observed for either CD4 + or CD8 + [14] . In our study, we observed no relative changes in CTL (CD3 + CD8 + cells) infiltration in carcinoma regions.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…They observed an anti-tumor effect and an indication of immune activation following HAL-BLC according to visual assessment of immunological markers (CD3 + , CD8 + , and CD4 + ), with observation of intratumoral CD3 + and CD8 + immune cell infiltration. However, quantification of the total number of CD3 + cells revealed significantly higher CD3 + infiltration in the control group than in the HAL-BLC group, but similar results were not observed for either CD4 + or CD8 + [14] . In our study, we observed no relative changes in CTL (CD3 + CD8 + cells) infiltration in carcinoma regions.…”
Section: Discussionmentioning
confidence: 56%
“…CTLs play a central role in antitumor immunity [17] . Lamy et al [14] used an orthotopic model of bladder cancer in rats to investigate immune cell infiltration in rats receiving HAL-assisted BLC. They observed an anti-tumor effect and an indication of immune activation following HAL-BLC according to visual assessment of immunological markers (CD3 + , CD8 + , and CD4 + ), with observation of intratumoral CD3 + and CD8 + immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that diagnostic doses of HAL and blue light can be combined with a checkpoint inhibitor to improve therapeutic efficacy. In an orthotopic rat model, 30 days positive antitumor effect was improved from 31% to 38% when PDD was combined with an intravesical anti-PD-L1 checkpoint inhibitor (74). Using HAL reduced the PpIX formation time to just 2 h by using just a fraction of the amount of 5-ALA (8 vs 180 mM) (75,76).…”
Section: Hexyl Aminolevulinate (Hal)mentioning
confidence: 99%
“…Lamy et al, studied if the use of hexaminolevulinate and blue light cystoscopy in an orthotopic rat model of bladder cancer may have therapeutic efficacy by modulation of a tumor-specific immune response and measured if its delivery in combination with a checkpoint inhibitor may enhance any effects observed. Positive anti-tumor effect was related to the timing of the process with a localization of CD3+ and CD8+ cells at long term: the effect was increased when delivered in combination with intravesical anti-PD-L1 (for more information, see [ 10 ]). Klimenko et al, describe the activity of (3S,4S)-14-Ethyl-9-(hydroxymethyl)−4,8,13,18-tetramethyl-20-oxo-3-phorbinepropanoic acid (ETPA) as a crucial metabolite of the North Pacific brittle stars Ophiura sarsii in a mouse model of glioblastoma.…”
mentioning
confidence: 99%